Regional adoptive immunotherapy with interleukin-2 and lymphokine-activated killer (LAK) cells for liver metastases - Keilholz, Ulrich; Scheibenbogen, Carmen; Brado, Matthias; Georgi, Peter; Maclachlan, David; Brado, Bernadett; Hunstein, Werner (European journal of cancer, 1994)
A phase lb trial of a novel regional approach to adoptive immunotherapy is reported. Patients with liver metastases received continuous high-dose infusion of interleukin-2 (IL-2) into the splenic artery or intravenous infusion with subsequent transfer of lymphokine-activated killer (LAK) cells into the portal vein or the hepatic artery. Trafficking studies revealed homogenous distribution of the LAK cells within the liver. The usual side-effects of IL-2 and LAK cells occurred without limiting liver toxicity. One partial (7+ months) and two complete responses (36 and 26+ months) were observed in 9 patients with metastases from cutaneous melanoma. None of 6 patients with metastases from ocular melanoma responded.